Inhibition of cytoplasmic and organellar protein synthesis in Toxoplasma gondii. Implications for the target of macrolide antibiotics. - Beckers, C J (1995)
We investigated potential targets for the activity of protein synthesis inhibitors against the protozoan parasite Toxoplasma gondii. Although nanomolar concentrations of azithromycin and clindamycin prevent replication of T. gondii in both cell culture and in vivo assays, no inhibition of protein labeling was observed in either extracellular or intracellular parasites treated with up to 100 microM drug for up to 24 h. Quantitative analysis of > 300 individual spots on two-dimensional gels revealed no proteins selectively depleted by 100 microM azithromycin. In contrast, cycloheximide inhibited protein synthesis in a dose-dependent manner. Nucleotide sequence analysis of the peptidyl transferase region from genes encoding the large subunit of the parasite's ribosomal RNA predict that the cytoplasmic ribosomes of T. gondii, like other eukaryotic ribosomes, should be resistant to macrolide antibiotics. Combining cycloheximide treatment with two-dimensional gel analysis revealed a small subset of parasite proteins likely to be synthesized on mitochondrial ribosomes. Synthesis of these proteins was inhibited by 100 microM tetracycline, but not by 100 microM azithromycin or clindamycin. Ribosomal DNA sequences believed to be derived from the T. gondii mitochondrial genome predict macrolide/lincosamide resistance. PCR amplification of total T. gondii DNA identified an additional class of prokaryotic-type ribosomal genes, similar to the plastid-like ribosomal genes of the Plasmodium falciparum. Ribosomes encoded by these genes are predicted to be sensitive to the lincosamide/macrolide class of antibiotics, and may serve as the functional target for azithromycin, clindamycin, and other protein synthesis inhibitors in Toxoplasma and related parasites.